Arsène Lupin gentleman-thief - Leblanc, Maurice 1864-1941 (Orion Fiction, 2021)
The year is 1905. Meet Arsene Lupin: a gentleman and a thief. An enemy to the rich and powerful; a friend to the poor - Arsene Lupin will stop at nothing until he gets what he wants. When Arsene Lupin is arrested, the police think it's all over. But the most dangerous place for Lupin is to be behind bars...